2021
DOI: 10.21203/rs.3.rs-861157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Biobased Polyol Type On The Properties of Polyurethane Hotmelt Adhesives For Footwear Joints

Abstract: The implementation of a Circular Economy model, promoted by the increasingly stricter European policies, demands a comprehensive approach to resource efficiency. In this sense, polyurethanes, one of the most used polymers worldwide, are strongly dependent of non-renewable fossil resources. Thus, boosting the production of new polyurethanes / a new polyurethane based on more sustainable raw materials is crucial to move towards the footwear industry decarbonisation. INESCOP, aware of the footwear industry’s envi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, the softening point of conventional HMPUR adhesives is around 55°C and the new CO 2 -based adhesives had similar softening points. 53,54…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the softening point of conventional HMPUR adhesives is around 55°C and the new CO 2 -based adhesives had similar softening points. 53,54…”
Section: Resultsmentioning
confidence: 99%
“…The use of plasma, both low-pressure and atmospheric plasma, achieved in physically and chemically modifying the rubber surface so that the adhesion values obtained were comparable to those obtained with conventional roughening and halogenation treatment. 11,54 However, it was observed that the halogenation treatment for adhesive joints with HMPUR could be more effective due to the adhesion failures obtained. This is because the adhesion failures (shown in Figure 14) obtained in these joints correspond to a mixture of a failure with half of the sole material torn and the failure of adhesion to the sole material (50A2/50M2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation